Serum stearic acid/palmitic acid ratio as a potential predictor of diabetes remission after Roux‐en‐Y gastric bypass in obesity. Issue 4 (22nd December 2016) - Zhao, Linjing; Ni, Yan; Yu, Haoyong; Zhang, Pin; Zhao, Aihua; Bao, Yuqian; Liu, Jiajian; Chen, Tianlu; Xie, Guoxiang; Panee, Jun; Chen, Wenlian; Rajani, Cynthia; et al.
Abstract : Endogenous fatty acid metabolism that results in elongation and desaturation lipid products is thought to play a role in the development of type 2 diabetes mellitus (T2DM). In this study, we evaluated the potential of estimated elongase and desaturase activities for use as predictive markers for T2DM remission after Roux‐en‐Y gastric bypass (RYGB). The results of a targeted metabolomics approach from 2 independent studies were used to calculate 24 serum FA concentration ratios (product/precursor). Gene expression data from an open public data set was also analyzed. In a longitudinal study of 38 obese diabetic patients with RYGB, we found higher baseline stearic acid/palmitic acid (S/P) ratio. This ratio reflects an elovl6‐encoded elongase enzyme activity that has been found to be associated with greater possibility for diabetes remission after RYGB [odds ratio, 2.16 (95% CI 1.10–4.26)], after adjustment for age, gender, body mass index, diabetes duration, glycosylated hemoglobin A1c, and fasting C‐peptide. Our results were validated by examination of postsurgical elovl6 gene expression in morbidly obese patients. The association of S/P with the metabolic status of obese individuals was further validated in a cross‐sectional cohort of 381 participants. In summary, higher baseline S/P was associated with greater probability of diabetes remission after RYGB and may serve as a diagnostic marker in preoperative patient assessment. —Zhao, L., Ni, Y., Yu, H., Zhang, P., Zhao, A., Bao, Y., Liu, J., Chen, T., Xie, G., Panee, J., Chen, W., Rajani, C., Wei, R., Su, M., Jia, W., Jia, W. Serum stearic acid/palmitic acid ratio as a potential predictor of diabetes remission after Roux‐en‐Y gastric bypass in obesity. FASEB J . 31, 1449–1460 (2017) www.fasebj.org